2019
DOI: 10.1111/jipb.12789
|View full text |Cite
|
Sign up to set email alerts
|

PEX16 contributions to peroxisome import and metabolism revealed by viable Arabidopsis pex16 mutants

Abstract: Peroxisomes rely on peroxins (PEX proteins) for biogenesis, importing membrane and matrix proteins, and fission. PEX16, which is implicated in peroxisomal membrane protein targeting and forming nascent peroxisomes from the endoplasmic reticulum (ER), is unusual among peroxins because it is inserted co‐translationally into the ER and localizes to both ER and peroxisomal membranes. PEX16 mutations in humans, yeast, and plants confer some common peroxisomal defects; however, apparent functional differences have i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Ces2e and Ces1 are carboxylesterases that play an important role in exogenous ester drug metabolism and endogenous lipid metabolism ( Lian et al, 2018 ), and their expression levels showed an increasing trend in this study. In addition, the disruption in the expression levels of the proteins Nudt19, Lonp2, and PEX16, which are related to mitochondrial and peroxisomal productivity ( Wu et al, 2018 ; Burkhart et al, 2019 ; Görigk et al, 2022 ), also reflected the metabolic disorders caused by AAI.…”
Section: Discussionmentioning
confidence: 99%
“…Ces2e and Ces1 are carboxylesterases that play an important role in exogenous ester drug metabolism and endogenous lipid metabolism ( Lian et al, 2018 ), and their expression levels showed an increasing trend in this study. In addition, the disruption in the expression levels of the proteins Nudt19, Lonp2, and PEX16, which are related to mitochondrial and peroxisomal productivity ( Wu et al, 2018 ; Burkhart et al, 2019 ; Görigk et al, 2022 ), also reflected the metabolic disorders caused by AAI.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to PEX3 and PEX19, Arabidopsis PEX16 assists in targeting PMPs that first insert into the ER [49]. Viable pex16 alleles show enlarged peroxisomes [50], and peroxisomes are enlarged or misshapen when PEX3, PEX16, or PEX19 levels are reduced via RNAi [51]. Exploration of PEX3 and PEX19 functions is complicated by gene duplications resulting in two isoforms of both peroxins in Arabidopsis [20,52].…”
Section: Emergence Of the Peroxisomal Proteome-transcription Translat...mentioning
confidence: 99%
“…Arabidopsis pex16 null mutants are inviable because of the essential role of peroxisomes in embryogenesis. Burkhart et al (2019) have identified two viable pex16 alleles, which allowed them to dissect the function of PEX16 in peroxisome protein import and growth beyond embryogenesis in Arabidopsis, and assess the functional domains of PEX16.…”
mentioning
confidence: 99%